Propuesta de mejoramiento vía terciaria UTP - Mundo Nuevo – la Bella, (Vereda la Bella, Pereira, Risaralda), mediante el prediseño de su construcción. (2021)
The work that was carried out contains a proposal for the pre-design of a footprint plate in hydraulic concrete, on the UTP Mundo Nuevo - La Bella road, for this the literature related to the subject was investigated in the databases, to know what background is present and its theoretical framework, through descriptive quantitative methodology, the work was developed, among the most relevant results of the research and of the different field works is that: for the calculations of a possible design, it was obtained by means of the vehicular capacity carried out that there is a value of 8,124,658 axles equivalent of 8.2 Tons in a period of 10 years, or therefore, the construction of a footprint plate will not make it functional in the long term.